Topical Application of ASPP 092, a Diarylheptanoid Isolated from Curcuma comosa Roxb, Accelerates Wound Healing - Waratta Hemtong; Aporn Chuncharunee; Gopinathan Pillai Sreekanth (MDPI AG, 2022)
Wound healing is the restorative process of skin or tissue injury, composed of the inflammatory, proliferative, maturation, and remodeling phases. The current study aimed to examine the efficacy of ASPP 092 (a well-characterized diarylheptanoid from Curcuma comosa Roxb) in modulating wound healing. Full-thickness excision wounds were made in rats and treated with either ASPP 092 (dose: 1 mg/mL and 2 mg/mL) or mupirocin (bioequivalent formulation). A control group treated with the vehicle (gel base) was also maintained. The healing efficacy of ASPP 092 was evaluated based on gross appearance, wound closure, and histopathology on days 3, 7, and 12 post-wounding. The expression of cyclooxygenase-2 (COX-2) among the groups was also determined on day 3 post-wounding. Our results suggest that ASPP 092 treatment accelerated wound healing, as evidenced by rapid wound closure, re-epithelialization, and granulation of tissue formation with fewer inflammatory cells. More fibroblasts, collagen fibers, and blood vessels originated with reduced COX-2 expression in the wounds, demonstrating the anti-inflammatory potential of ASPP 092 in experimental wounds. In conclusion, our findings, for the first time, preliminarily identified the potential of ASPP 092 in accelerating wound healing; however, more detailed studies on its mechanism of action in wound healing are required.